2007
DOI: 10.1002/chir.20458
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism of diglycosyl dichalcogenides in solution and solid state

Abstract: Solution and solid-state CD spectra of nine peracetylated and deacetalyted diglycosyl disulfides were measured to study the relationship between the low-energy CD transitions (n1-->sigma*(S--S) and n2-->sigma*(S--S)) and helicity of the inherently chiral disulfide chromophore as perturbed by chiral carbohydrate moieties. The solid-state CD spectra were directly correlated with the reported X-ray structures of Ac4GlcSSGlcAc4 and Ac4GlcSSGalAc4, and the CD data revealed that all the disulfides have M helicity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
(53 reference statements)
2
18
0
Order By: Relevance
“…An analysis of the MO transitions that determine this band has shown that this band is mostly determined by the so‐called n 1 →σ* S−S transition (where n 1 is an antiphase combination of the two p‐type sulfur lone‐pair atomic orbitals—the HOMO in this particular case). While the intensity of this band is overestimated by our BP86/TZP calculations, the sign of the band is in agreement with the quadrant rule formulated by Linderberg and Michl and also with the conclusions drawn elsewhere …”
Section: Improved Conformer Resolutionsupporting
confidence: 92%
See 1 more Smart Citation
“…An analysis of the MO transitions that determine this band has shown that this band is mostly determined by the so‐called n 1 →σ* S−S transition (where n 1 is an antiphase combination of the two p‐type sulfur lone‐pair atomic orbitals—the HOMO in this particular case). While the intensity of this band is overestimated by our BP86/TZP calculations, the sign of the band is in agreement with the quadrant rule formulated by Linderberg and Michl and also with the conclusions drawn elsewhere …”
Section: Improved Conformer Resolutionsupporting
confidence: 92%
“…While the intensity of this band is overestimated by our BP86/TZP calculations, the sign of the band is in agreement with the quadrant rule formulated by Linderberg and Michl 29 and also with the conclusions drawn elsewhere. 30,31…”
Section: Improved Conformer Resolutionmentioning
confidence: 99%
“…In solution both M and P forms can occur in equilibrium. Our preliminary NOE studies have, however, indicated 17 Pinto and co-workers 2 came to a similar conclusion for (1!4)-linked disulfide-and selenosulfide disaccharides. The C2-C1-S1-S2 and S1-S2-C21-C22 torsions indicate syn and anti geometry, respectively, the latter displaying more deviation from the ideal value (157°rather than 180°) just as in the symmetrical molecule 2.…”
Section: Resultssupporting
confidence: 58%
“…Pellet techniques have been used in many laboratories, for a variety of samples including biomolecules, [32][33][34][35][36][37][38][39][40][41][42][43] both in the UV-vis (ECD) and in the IR (VCD).…”
Section: Pelletsmentioning
confidence: 99%